Stepchildren And Incest: Law Enforcement Efforts Against Sexual Abuse In Families (A Case Study on the Decisions of Wonogiri State Court, Idi Sharia Court, and Banda Aceh Sharia Court) - Natangsa Surbakti; Nerisia Bunga Samodra; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2022)
ABSTRACT Purpose of the study: This paper aims to analyze three cases of sexual violence perpetrated by stepfathers to underage stepdaughters (incest) in Wonogiri Regency and Aceh Province. Methodology: This legal research used a normative juridical approach. The literary legal research was conducted by studying literary materials or secondary data. The writers used the Legal System Theory of Lawrence M. Friedman. Results: Friedman opined that there are four elements in law enforcement. In the analyzed cases, they were: (1) legal structure: the court and sharia courts, (2) legal substance: laws used by judges in deciding upon the cases, namely Law No. 17 of 2016 and Aceh Qanun No. 6 of 2014, (3) legal culture: society had a role in enforcing the law in these cases, as the police force, general prosecutors, and judges have carried out their functions well, and (4) legal impact: the strict implementation of punishments will bring a greater deterrent effect on the perpetrators. Some factors triggered the crime of incest to happen, namely: (1) the perpetrator, (2) the victims as underage children are deemed powerless against the perpetrator, and (3) the environmental condition where the houses were deserted. Applications of this study: This analysis can be used by the government to better enforce the law on sexual violence in families in Indonesia. Novelty/Originality of this study: This writing analyzes three cases using two aspects, namely Friedman's theory and judicial consideration in making decisions. Keywords: Stepchild, Law Enforcement, Sexual Violence, Incest.